Prevalence of Anxiety and Depression in Cardiac Patients Undergoing Coronary Bypass Surgery (Medical Forum Monthly, 2022)
Objective: To evaluate the prevalence of psychiatric comorbidity pre and post-surgery in CAD patients undergoing coronary artery bypass grafting.Study Design: A prospective studyPlace and Duration of Study: This study was conducted at the Department of Cardiology, Ch.Pervaiz Elahi Institute of Cardiology Multan for 1 year from 8th April 2019 to 8th April 2020.Materials and Methods: A total of 60 patients with coronary artery disease were included in the study that was undergoing coronary artery bypass grafting. All the patients awaiting CABG or undergoing CABG were tested for depression and anxiety by Beck’s Depression Inventory and Beck’s Anxiety Inventory. The patients were admitted to the hospital two days before the surgery and tests were performed after 1 day before the surgery and 3rd day after the surgery with the in-hospital patients. These tests were repeated 1 week and 1 month after the surgery with out-hospital patients.Results: The average depression and anxiety scores before surgery were 7.21±4.33 and 10.12±6.53 respectively. These scores increase on the 3rd day after surgery, 11.24±5.22 and 17.09±8.92 respectively. However, the scores after 1 week and 1 month did not differ significantly. Similarly, patients showed more depression and anxiety symptoms post-surgery. No significant difference was found in the relation of depression and anxiety scores with the age and gender of subjects.Conclusion: Depression and anxiety in CAD patients undergoing CABG are not related to heart disease, therefore early management and mental support can improve these conditions and lifestyles after surgery.